Comparative characteristics of the spatial grid-cable steel-concrete composite slab - Gasii, G. M (Видавництво Львівської політехніки, 2016)
The paper studies the theoretical calculations of the material and human resources that is needed for manufacturing and construction the spatial grid-cable steel-concrete composite slab. Some comparative characteristics of the construction were estimated such as weight, bearing capacity etc. The spatial grid-cable steel-concrete composite slab is the new kind of a construction for long-span roofs and shells. The feature of the construction is in its the constructive concept. This construction consists of the diagonal members, the top and the bottom chords. The spatial grid-cable steel-concrete composite slab consists of some number of the spatial steel-concrete modules, which are a combination of reinforced concrete slabs and steel diagonal members that are made of segments of steel tubes. The modules are connected to each other in nodes by using special bolted connections. The top chord are made of reinforced concrete slab and the bottom chord are made of steel cables. Calculations of technical and economic indicators were solved on the example of one section of the roof of the size of 30×6 m. These data demonstrate the effectiveness and feasibility of studied structures in the shells of buildings and structures of various function. Studies show that the use of the spatial grid-cable steel-concrete composite slab allows reducing the weight of the roof by 32–72 %, the laboriousness – by 10% compared to analog. Наведено результати теоретичних розрахунків матеріальних і трудових ресурсів, які затрачаються на виготовлення і зведення структурно-вантових сталезалізобетонних конструкцій покриттів будівель та споруд різного призначення. Також було визначенно деякі порівняльні характеристики досліджуваної конструкції, наприклад, такі як вага, несуча здатність тощо. Просторова структурно-вантова сталезалізобетонна плита є новим типом збірних конструкцій для великопрольотних покриттів і оболонок. Особливість такої конструкції полягає в її конструктивному рішенні. Така конструкція складається з просторової решітки, верхнього і нижнього поясів. Просторова структурно-вантова сталезалізобетонна плита складається з певної кількості просторових сталезалізобетонних модулів, які являють собою поєднання залізобетонних плит і сталевих стрижнів, виготовлених з відрізків сталевих труб. Модулі поєднуються один з одним у вузлах за допомогою спеціальних болтових з’єднань. Як верхній пояс використовують залізобетонну плиту, а як нижній – сталевий канат. Техніко-економічні показники розраховано для однієї секції покриття з розмірами у плані 30×6 м. Отримані дані свідчать про ефективність та доцільність застосування досліджуваних конструкцій у покриттях будівель і споруд різного призначення. Результати досліджень показують, що із застосуванням структурно-вантових сталезалізобетонних конструкцій вага покриття знижується на 32–72%, затрати праці – на 10% порівняно з аналогом.
Keywords: steel-concrete composite; structure; cable; slab; lattice; laboriousness; сталезалізобетон; структура; ванта; плита; решітка; трудомісткість